Thinking space differently: Deleuze's Möbius topology for a theorisation of the encounter. Issue 1 (26th May 2019) - Cockayne, Daniel G.; Ruez, Derek; Secor, Anna J.
Abstract : The relation between difference and space has long been and continues to be an animating problem in theoretical and political conversations across the discipline of geography, including in much recent work on encounter. In this paper, we make the case for the value of a less explored angle on space in Deleuze's work, which we call the topologies of space‐as‐difference. We highlight the Möbius strip as a central figure in his ontological system, and we show the significance of this topological structure both for understanding key Deleuzian concepts, such as the virtual and actual, and for understanding space and difference in productive ways. We demonstrate this by showing how Deleuzian topologies of difference enable us to further theorise the encounter – a key theme in recent geographical scholarship – as spatial and embodied, connecting up with material feminism and work on the skin, touch, and breath. We suggest that Deleuze's concept of space‐as‐difference thus contributes to the intensification of relational and topological approaches to space that are currently shaping the discipline.